Problems in the Field of Energy and Ways to Overcome Them - Boymurodova Nilufar Murodullayevna (Genius Publishing Group, 2022)
This article explains the problems in the electric power industry. The current problems of the energy sector in the world and their research, the views of scientists are covered. Proposals and recommendations for the development of renewable energy sources in Uzbekistan are provided.
Keywords: Solar Energy; Wind Energy; Power Plant; Energy Industries